Investigation of new band parameters with temperature dependence for self-broadened methane gas in the range 9000 to 14,000cm -1 (0.71 to 1.1μm) - Bowles, N; Passmore, R; Smith, K; Williams, G; Calcutt, S; Irwin, P (2012)
This paper describes new measurements and modelling of the absorption of methane gas, one of the most important gases observed in the atmospheres of the outer planets and Titan, between 9000 and 14,000cm -1 (0.7 to 1.1μm) and compares them with current best available spectral models.A series of methane spectra were measured at the UK's Natural Environment Research Council (NERC) Molecular Spectroscopy Facility (based at the Rutherford Appleton Laboratory, Oxfordshire, UK) using a Brüker 125HR Fourier transform spectrometer. To approximate the conditions found in outer planet atmospheres, the spectra were measured over a wide range of pressures (5bar to 38mbar) and temperatures (290-100K) with path lengths of 19.3, 17.6, 16.0 and 14.4m. The spectra were recorded at a moderate resolution of 0.12cm -1 and then averaged to 10cm -1 resolution prior to fitting a series of increasingly complex band-models including temperature dependence. Using the most complex model, a Goody line distribution with a Voigt line shape and two lower energy state levels, the typical rms residual error in the fit is between 0.01 and 0.02 in the wings of the main absorption bands.The new spectral parameters were then compared with the measured spectra and spectra calculated using existing data and shown to be able to accurately reproduce the measured absorption. The improvement in the temperature dependence included in the model is demonstrated by comparison with existing cold methane spectral data for a typical Jovian path. © 2012 Elsevier Ltd.